Application of Mapping and Pinboard Mapping for Observation of Corn Plantation Root at Inceptisol Soil, Tlogomas, Malang - Susilawati, Siti Azizah (Forum Geografi, 2004)
This research was carried out in Tlogomas, Malang. The goal of this study is to find out how interaction between root and soil physics condition in inceptisol. This interaction will give implication in roots distribution of corn in the soil. This research using mapping and pinboard tehnique to capture the root distribution in the soil and lassified in big, middle, and small roots. Mapping technique used to count number of root that shown in the soil profile. Pinboard technique used to get roots and divide into grid system to measure roots distribution each depth of soil. The result of this research shows that soil dry weight decreasing into deeper soil. Horisontally, root distributed 50 cm from the steam. Mapping and pinboard technique that applied together will give more effecctive information about root distribution.